FSI Modeling Approach to Develop Right Ventricle Pulmonary Valve Replacement Surgical Procedures with a Contracting Actuator and Improve Ventricle Ejection Fraction; Procedia Engineering; Vol. 126: Proceedings of the 7th International Conference on Fluid Mechanics May 24-27, 2015, Qingdao, China - Chun Yang; Dalin Tang; Vasiljev N. V. Nikolay Vladimirovich; Rathod R. Rahul; Geva T. Tal; del Nido P. J. Pedro (2015, 2015)
Title screen